2015
DOI: 10.1007/s00253-015-6941-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of ribosome-inactivating proteins and their possible applications as antimicrobial, anticancer, and anti-pest agents and in neuroscience research

Abstract: Ribosome-inactivating proteins (RIPs) are enzymes which depurinate ribosomal RNA (rRNA), thus impeding the process of translation resulting in inhibition of protein synthesis. They are produced by various organisms including plants, fungi and bacteria. RIPs from plants are linked to plant defense due to their antiviral, antifungal, antibacterial, and insecticidal activities in which they can be applied in agriculture to combat microbial pathogens and pests. Their anticancer, antiviral, embryotoxic, and abortif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 190 publications
0
19
0
4
Order By: Relevance
“…In agriculture, It is demonstrated in vitro and in transgenic plants that RIPs have been connected to defense by antifungal, antibacterial, antiviral and insecticidal activities ( Stevens et al, 1981 ; Wang and Tumer, 2000 ; Choudhary N.L. et al, 2008 ; Akkouh et al, 2015 ). These studies have conferred a wide knowledge base for comprehending the medicinal and biochemical properties of RIPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agriculture, It is demonstrated in vitro and in transgenic plants that RIPs have been connected to defense by antifungal, antibacterial, antiviral and insecticidal activities ( Stevens et al, 1981 ; Wang and Tumer, 2000 ; Choudhary N.L. et al, 2008 ; Akkouh et al, 2015 ). These studies have conferred a wide knowledge base for comprehending the medicinal and biochemical properties of RIPs.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2 , the proposed model for the role of RIPs in defense against pathogens showed that various RIPs have shown unique bioactive properties, including antibacterial, antifungal, antiviral, and insecticidal activity ( Stirpe and Battelli, 2006 ; Shu et al, 2009 ; Akkouh et al, 2015 ). A large number of studies suggest that the expression of RIPs could be activated by some factors, such as viral infection, phytohormones, senescence, development, and environmental stress ( Reinbothe et al, 1994 ; Girbés et al, 1996 ; Stirpe et al, 1996 ; Rippmann et al, 1997 ; Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike plant lectins , none of the mushroom lectins isolated to date displays antifungal activity. Fungal ribosome-inactivating proteins and their plant counterparts (Stirpe andBattelli, 2006, Stirpe 2013) have dissimilar N-terminal sequences but have biological activities in common like antimicrobial, anticancer and antiviral activities (Akkouh et al 2015). Fungal ribonucleases display anticancer and HIV-1 reverse transcriptase activities like ribonucleases of other origins (Fiorini et al, 2014(Fiorini et al, , 2015.…”
Section: Resultsmentioning
confidence: 99%
“…MAP30 has been shown to inhibit HIV; it also inhibits the cell proliferation of a panel of tumor cells in vitro and in vivo (Fang and Ng 2011; Fang et al 2012a, b). Recent studies have also shown that MAP30 can inhibit the herpes simplex virus and pathogenic fungus (Akkouh et al 2015; Wang et al 2016), and could induce cell death (Fan et al 2015). Taken together, the results of previous studies have suggested that the anti-viral activities are the most characterized of MAP30, especially activities against HIV, HBV, and tumor cell proliferation (Lee-Huang et al 1995; Fan et al 2008, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that non-glycosylated MAP30 protein is as active as the glycosylated natural protein, and recombinant MAP30 possesses anti-HIV, anti-HBV, anti-tumor and apoptosis induction activities (Lee-Huang et al 1995; Fan et al 2008, 2009). Recent studies have also revealed that MAP30 exerts activities against the herpes simplex virus and pathogenic fungus (Akkouh et al 2015; Wang et al 2016), and can induce cell-cycle arrest and apoptosis in human lung carcinoma cells (Fan et al 2015). However, the effects of recombinant MAP30 in terms of antibacterial activities and possible replacement of antibiotics are unknown, and the toxicity and immunogenicity of MAP30 have also never been studied.…”
Section: Introductionmentioning
confidence: 99%